Retention intention of nurses in government hospitals of the Jaffna district, Sri Lanka - Wijethunga, W.M.C.C.; Thenuwara, T.H.T.N.; Rajeev, G.; Kamalarupan, L. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2025)
Nurses form the backbone of health care systems, and their intention to stay directly affects care quality. Despite many nurses leaving the profession, local literature has paid little attention to this issue. Objective: This study aimed to assess the retention intention of nurses working at government hospitals in the Jaffna District. Methods: A descriptive cross-sectional study was conducted among 282 nurses selected through stratified sampling from secondary and tertiary hospitals in Jaffna District. Data was collected using a self-administered questionnaire. Retention Intention was assessed with a Dichotomous (Yes/No) question, and its association with participant sociodemographic characteristics was analysed with SPSS version 26. Descriptive statistics, Chi-square tests, and t-tests were applied. Ethical approval was obtained from the Ethics Review Committee of the Faculty of Medicine, University of Jaffna. Results: The mean age of nurses intending to stay (35.8 ± 8.0 years) was significantly higher than those intending to leave (29.9 ± 3.4 years), p < 0.001. Among participants, 38.8% (n=109) were female, 53.9%(n=152) were Tamil, 57.4%(n=162) were married, 69.1%(n=195) worked in tertiary hospitals, and 50.7% (n=143) were from outside Jaffna District. Overall, 57.1%(n=161) intended to stay, while 42.9%(n=121) preferred to leave. Main reasons for staying included job satisfaction (45.96%, n=127) and financial stability (24.8%, n=70), while most intending to leave sought overseas employment (89.25%, n=252). Factors significantly associated with retention included ethnicity, nursing grade, previous experience, civil status, having children, hometown, accommodation, and transport (p < 0.05). Sex was not significant. A chi-square test showed a significant association between hospital type and retention (p=0.030), with tertiary hospital nurses more likely to remain. Conclusion: Nurses in tertiary hospitals were more likely to remain compared to those in secondary hospitals. Strategies targeting workplace conditions, career development, and supportive policies are essential to improve nurse retention in secondary hospitals.
Keywords: Nurse; Tertiary Hospital; Secondary Hospital; Retention Intention